The role of high-N orbits in superdeformed states - Bengtsson, Tord; Ragnarsson, Ingemar; Åberg, Sven (Physics Letters B, 1988)
It is investigated how particles in high-N shells affect the moment of inertia, A figure is presented(2), and the quadrupole moment, Q0, of superdeformed high-spin states. The different behaviour of A figure is presented(2) versus the rotational frequency observed for superdeformed states in 152Dy and 149Gd is explained in terms of different occupations of a few high-N orbits. Predictions for A figure is presented(2) and Q0 for the neighbouring nucleus 148Eu are presented.